(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Family Adoption Programme (FAP) aims to provide an experiential learning opportunity to Indian medical graduates towards community-based health care and thereby equity in health. This paper describes the output of FAP implementation in Phase I MBBS curriculum in a medical college of western India. Methods: A brief orientation was conducted on the needs and competencies of FAP as recommended by the National Medical Commission of India which was followed by sensitization of the students to the FAP proforma prepared by the department along with hands on practice. Department planned and conducted periodic FAP visits for students along with their assigned mentors at the selected nearby two villages. During these visits, students interacted with the families and details regarding health profile of the family were documented. Students wrote reflection on FAP Visits in log book and were reviewed by faculties. Feedback assessment was done using Google link. Results: A total 100 students were enrolled in FAP and out of those 92 submitted the feedback through Google link. M:F ratio was 1:1. Out of 92 responses 80% students responded that FAP was a very good experience and would like to be part of such activity throughout the professional years. Conclusion: Implementation of FAP requires meticulous planning, intersectoral co-ordination, good sensitisation, and training activities in advance.